Crossing heritages: drystone walls in cultural tourism and geo-tourism - Rosendahl, Stefan (2021)
The aim of cultural tourism is the cultural heritage. This heritage can consist of monuments in cities, for instance, and also of vernacular heritage which is found in rural areas. The drystone walls, often existing in regions where slopes prevail, are splendid examples of this group of heritage. Their role in cultural vernacular heritage is that they are made by man to make agriculture possible in difficult terrain creating plane areas in slopes, to retain surface and subsurface water as a reserve e.g. for the plantation and protection against wildfires, to protect agricultural areas in lower places against falling rocks and erosion by torrents, and so on. On the other hand, they also belong to the natural geological heritage because they are made of local stones, the geological setting of an area determines if such a wall is necessary or not, they interfere with the surface and subsurface water flows, they slow down erosional processes, they mould typical landscapes, and they create a lot of ecological niches and habitats for animals and plants. Therefore, drystone walls represent a link between cultural-vernacular and natural-geological heritage. Stone wall terraces are an expression of the history and the culture of the local people and present environmental, social and economic benefits. They may offer touristic opportunities, contributing to their renewal and survival. Their cultural value was recognized by the UNESCO in 2018 by the declaration of the “art of drystone walling, knowledge and techniques” as Intangible Cultural Heritage of Humanity.